Prognosis of Bell Palsy: A Clinical, Neurophysiological, and Ultrasound Study. Issue 6 (November 2018) - Zaki, Maha A.; Elkholy, Saly H.; Abokrysha, Noha T.; Khalil, Alshaimaa Sobhi; Nawito, Amani M.; Magharef, Nagween W.; Kishk, Nirmeen A.
Abstract : Purpose: Bell palsy is the most common cause of acute facial nerve paralysis. Ultrasound has proved its ability in detecting structural lesions along the course of the affected nerves.The current work aimed at studying the accuracy of ultrasound to predict the prognosis of Bell palsy in correlation to the clinical scale and nerve conduction studies. Methods: The study included 20 cases of acute Bell palsy treated with prednisolone and physiotherapy. The participants were examined using the House–Brackmann (HB) scale, electrophysiologically and neurosonologically in the affected side and healthy side that served as a control. Results: There was significant correlation between HB outcomes with onset of HB results. There was significant increase in the distal facial nerve diameter on the affected side compared with the normal side ( P < 0.001). Although ultrasound at onset did not predict the outcome, nerve conduction studies did predict the outcome. Conclusions: Baseline HB clinical assessment of Bell palsy gives information on the clinical outcome of the disease. In addition to that, initial nerve conduction studies proved to be superior to ultrasound in predicting the outcome.